"Kids these days pretend to be grownups" (dekkaedaet): sexual control and negotiation among young Thai female students - Worawalan Waratworawan; Pimpawun Boonmongkon; Nattharat Samoh; Petcharat Promnart; Thomas E. Guadamuz (BMC, 2021)
Abstract Background Young Thai women are growing up amidst conflicting influences of globalization and traditional Thai culture. They experience confusion about which aspects of their sexuality they can express and must hide. This study examined forms of sexual control and sexual negotiation among young Thai women in secondary and vocational schools. Methods Semi-structured interviews and focus group discussions were conducted among 13-to 18-year-old female students attending secondary and vocational schools in six regions of Thailand. Additional semi-structured interviews were conducted with instructors of sex education, school administrators, and parents of students. NVIVO 10 was used to manage, code and assist with data analysis. Results Socio-cultural control on young women's sexualities was found from members of their families, schools, communities, and other students. Young women expressing their sexualities openly through verbal expressions, clothing, and behaviors were deemed negatively and stigmatized as dekkaedaet or "kids pretending to be grownups" as it is believed that they are too young and too immature to be responsible for their own decisions on their bodies and sexuality. This dominant discourse subsequently stigmatize and embarrass sexually active women. However, some young women try to negotiate and create options, by utilizing strategies that ensure secrecy. Conclusion Comprehensive sexuality education is needed and should be based on the respect for human dignity and sexual and reproductive rights.